Diagnostic and management considerations in the modern patient with AIDS: a case of concurrent disseminated Kaposi sarcoma and colesional Cryptococcus neoformans. Issue 4 (14th April 2020) - Williams, Samuel Clay; Sweeney, Jacob; Parameswaran, Lalitha
Abstract : In the era of highly active antiretroviral therapy (HAART), disseminated Kaposi sarcoma (KS) has become much rarer in the USA. We report a case of a 34-year-old man with KS of the skin, oropharynx, lung and rectum. Within the same lung nodule, we discovered significant burden of colesional Cryptococcus neoformans, in the context of a positive asymptomatic cryptococcal antigenemia, which was a previously unreported occurrence. The gold standard of treatment for KS continues to be HAART. The role of chemotherapy is still controversial. In addition, a cryptococcal antigen screen-and-treat approach with fluconazole is still not routinely recommended in the USA to prevent serious meningeal disease despite recent studies showing efficacy and applicability. We discuss both issues here and the outcome of our patient. We also present the patient's own unique perspective in dealing with the ramifications of these diagnoses.